Legality of therapeutic contract of stem cell treatment in Indonesia - Ahdiana Yuni Lestari; Danang Wahyu Muhammad; Izzy Al Kautsar; Siti Ismijati Jenie (Intelektual Pustaka Media Utama, 2023)
This study analyzed the purposes and functions of stem cell treatment arrangements in Indonesian national law and then describe the characteristics of therapeutic agreements between patients and elements of health services against the legal terms of the agreement based on the Civil Code. This study used a normative juridical research method. The results of this study are: i) in terms of stem cell treatment procedures, only some can get services and treatment because the procedure is very complicated and lengthy. Hence, the purpose and function of regulating the implementation of stem cell treatment in Indonesia are to provide legal certainty and protection law to the public and health service providers; ii) the conditions for the validity of a stem cell Therapeutic agreement must be based on the criteria specified in Article 1,320 of the Civil Code, then the elements of the parties that bind themselves; the skills of the parties; particular object, and lawful cause must be clear, and iii) the type of therapeutic contract that can maintain the honor of the parties is the